Pengaruh Kepemilikan Institusional, Transfer Pricing, dan Pertumbuhan Penjualan terhadap Penghindaran Pajak - Butar-Butar, Obed Edom; Sunarto, Sunarto; Kwartarani, Yunita; Rahmadania, Siti Aisyah Nurrizqi (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This research aims to analyze the influence of Institutional Ownership, Transfer Pricing and Sales Growth on Tax Avoidance. This type of research is quantitative research with secondary data sources. The population in this research is non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (BEI) in 2018-2022. The sample selection method used in this research was purposive sampling so that the final sample obtained was 12 companies with a research period of 5 years. The research results show that the variables Institutional Ownership, Transfer Pricing and Sales Growth simultaneously influence Tax Avoidance. Then, partially, the Institutional Ownership and Transfer Pricing variables have no effect on Tax Avoidance. Meanwhile, Sales Growth influences Tax Avoidance.